2014
DOI: 10.3390/ijms151223909
|View full text |Cite
|
Sign up to set email alerts
|

PLGA Biodegradable Nanoparticles Containing Perphenazine or Chlorpromazine Hydrochloride: Effect of Formulation and Release

Abstract: In our study, poly(dl-lactide-co-glycolide) (PLGA) nanoparticles loaded with perphenazine (PPH) and chlorpromazine hydrochloride (CPZ-HCl) were formulated by emulsion solvent evaporation technique. The effect of various processing variables, including PLGA concentration, theoretical drug loading, poly(vinyl alcohol) (PVA) concentration and the power of sonication were assessed systematically to obtain higher encapsulation efficiency and to minimize the nanoparticles size. By the optimization formulation proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 32 publications
10
36
0
Order By: Relevance
“…In our study, we observed decrease in PDI with high concentration of PVA (trial 1, 7) which is also reported by Hylayqa [12] where high concentration of PVA showed decrease in PDI values for the same amount of PLGA, but the effect in our case is due to high volume of organic solvent used which assured the complete solubility of the polymer. …”
Section: Influence On Polydispersity Indexsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, we observed decrease in PDI with high concentration of PVA (trial 1, 7) which is also reported by Hylayqa [12] where high concentration of PVA showed decrease in PDI values for the same amount of PLGA, but the effect in our case is due to high volume of organic solvent used which assured the complete solubility of the polymer. …”
Section: Influence On Polydispersity Indexsupporting
confidence: 89%
“…An increase in the mean particle size was observed when increasing concentration of PLGA was used for all the amount of PVA in the formulation (1-3%). It was reported that an increase in the amount of PVA in the formulation may lead to the smaller particle size due to tight surface that is formed from PVA macromolecular chains at high concentration [12].…”
Section: Influence On Particle Sizementioning
confidence: 99%
“…This is due to the size of the nanoparticles decreasing with an increase in PVA loading ( Figure 2A). The smaller the size of the nanoparticles the less DSF they can encapsulate and thus the lower the encapsulation efficiency [59]. Furthermore, increasing the loading of PVA increases the concentration of residual PVA [60], which binds to the DSF limiting it's encapsulation in the PLGA [61].…”
Section: Encapsulation Efficiency Of the 10% W/w Dsf-loaded Plga Nanomentioning
confidence: 99%
“…The polydispersity index of the obtained nanoparticles ranged between 0.14 and 0.23, verifying in all cases the small polydispersity of the SLN solutions. It is well known that size influences both cell uptake and drug release kinetics in nanoparticles and other particulate systems [31][32][33]. Accordingly, it is desirable to attain low polydispersity since this is expected to result in a more predictable and homogeneous behavior within the targeted biological system.…”
Section: Synthesis and Characterization Of The Slnmentioning
confidence: 99%